Selection of Bradyrhizobium sp. isolates due to their effect on maize under agricultural drought conditions in Sancti Spíritus, Cuba - Bécquer, C. J.; Ávila, U.; Galdo, Yaldreisy; Quintana, Maribel; Álvarez, Orquidia; Puentes, Adelaida; Medinilla, F.; Mirabal, Analeidis (Cuban Journal of Agricultural Science, 2017)
A field experiment was conducted in Sancti Spíritus, Cuba, under agricultural drought conditions, in order to evaluate the effect of inoculation on maize with five Bradyrhizobium sp. isolates, from forage legumes of an arid cattle rearing ecosystem from Holguín, and to select the treatments with the best positive effect on the agro-productive variables. TGH maize variety was used. Isolates were grown in a solid yeast-mannitol medium and re-suspended in a liquid medium up to 106–108 cfu/mL. It was inoculated when the seed (6 days) was germinated with doses of 8-10 mL/plant. Conventional cultivation labors were carried out, with seeding rate of 12 kg/ha and a seeding frame of 50 cm between furrows. Each plot measured 2 m x 4 m and four irrigations were applied.An experimental design of random blocks was used, with 7 treatments and 3 replicates. The control was fertilized with NH4NO3 (150 kgNa/ha), absolute control and 5 inoculated treatments. Differences between means were determined with LSD test of Fisher. The evaluated variables were aerial dry weight, increase of aerial dry weight regarding absolute control, stem length, grain yield, increase of grain yield with respect to absolute control and weight of 1000 seeds. It should be noted that the aerial dry weight increase regarding absolute control in Ho9 was 21 %. The increaseof the grain yield with respect to the absolute control was 10 and 20 % in Ho13 and Ho5, respectively. It is concluded that Ho5 and Ho13 isolates had a positive effect on grain yield, and to a lesser extent, Ho1 and Ho9, in cob length and increase of aerial dry weight, respectively. Future field experiments, under conditions of drought with the Ho5 and Ho13 isolates, are recommended in different soil types of Sancti Spíritus province.Key words: Bradyrhizobium sp., agricultural drought, grain yield